Epidemiology and In Vitro Activity of Ceftazidime/Avibactam, Meropenem/Vaborbactam and Imipenem/Relebactam against KPC-Producing K. pneumoniae Collected from Bacteremic Patients, 2018 to 2020 - Federica Bovo; Donatella Lombardo; Tiziana Lazzarotto; Simone Ambretti; Paolo Gaibani (Antibiotics, 2022)
The management of KPC-producing K. pneumoniae (KPC-Kp) in bloodstream infections (BSIs) represent a serious clinical challenge. In this study, the aim is to assess the incidence of resistance to novel β-lactams-β-lactamase inhibitor combinations (βL-βLICs), such as ceftazidime-avibactam (CAZ-AVI), meropenem-vaborbactam (MER-VAB) and imipenem-relebactam (IMI-REL), in KPC-Kp strains collected during a three-year period from patients with bacteremia. KPC-Kp strains resistant to βL-βLICs were selected for whole-genome sequencing. A total of 133 K. pneumoniae strains were isolated, and KPC-Kp strains were the most represented (87.2%). In 2018, resistance to CAZ-AVI and MER-VAB was 6.5% and 14.5%, respectively. In 2019, KPC-Kp resistance to CAZ-AVI and MER-VAB remained at low levels, with values of 12.9% and 3.2%, respectively. During 2020, CAZ-AVI resistance was detected in 2/23 of KPC-Kp strains (8.7%). IMI-REL was the most active βL-βLIC, inhibiting >98% of the isolates, while CAZ-AVI and MER-VAB inhibited 87–93% and 85–97% of the KPC producers, respectively. Correlations between genotypic traits and resistance to βL-βLICs showed that KPC-Kp strains resistant to CAZ-AVI harbored a mutation within the blaKPC-3 gene, while all KPC-Kp strains resistant to CAZ-AVI, MER-VAB and/or IMI-REL carried the blaKPC-3 gene. Moreover, genetic analysis of porin genes showed that 14/16 of KPC-Kp resistant isolates possessed a truncated OmpK35 and glycine (G) and aspartic acid (D) insertions at positions 134–135 within OmpK36, whereas 2/16 displayed truncated OmpK35 and OmpK36 porins. Novel βL-βLICs are promising agents against KPC-Kp infections; however, the emergence of resistance to these agents highlights the need for continuous surveillance and application of enhanced antimicrobial stewardship.